ANALISIS PENGARUH GEOMETRI PAD DAN VARIASI KECEPATAN RODA TERHADAP TEMPERATUR KAMPAS REM CAKRAM: EFFECT OF PAD GEOMETRY AND WHEEL ROTATION SPEED VARIATIONS ON DISC BRAKE PAD TEMPERATURE - Mohammad Dzakiyul Fikri zaki; Eko (Jurnal Teknik Mesin, 2025)
The study aims to analyze how variations in wheel rotation speed and disc pad geometry affect brake pad temperature. During the braking process, heat is generated due to friction. If not managed properly, this heat can diminish braking performance and accelerate brake pad wear.Tests were conducted at four different motor rotation speeds: 1000 RPM, 1500 RPM, 2000 RPM, and 2500 RPM. The test system was designed using a braking system demonstration tool equipped with speed sensors and temperature sensors. This setup was connected to an Arduino microcontroller, allowing real-time data to be displayed via a Graphical User Interface (GUI) in MATLAB.The results indicated that both brake pad geometry and wheel rotation speed significantly impact temperature. Standard brake pads displayed the highest temperature at 2500 RPM, reaching 63.33°C. In contrast, brake pads with holes demonstrated superior performance, producing the lowest temperature of only 43.00°C. As the wheel's rotational speed increased, the temperature on standard pads rose from 36.67°C at 1000 RPM to 63.33°C at 2500 RPM. This indicates that RPM is a primary factor in heat generation due to friction. The MATLAB GUI effectively visualized the relationship between RPM and temperature, facilitating the analysis and evaluation of the data.